(untitled) (Research, Society and Development, 2022)
Inga laurina Willd, belongs to the Fabaceae family, popularly used against fungal infections, several flavonic compounds have already been isolated from all its parts, but there are few studies that evaluate the pharmacokinetic, toxicological properties and their biological activities of these, due to this, this This article aims to evaluate such properties of flavonic compounds isolated from Inga laurina leaves. ChemSketch software, PreADMET, PASS online and Mcule databases were used. The results showed that Gallocatechin-(4α-8)-4-O-methylgallocatechin, Gallocatechin-(2®0®7,4®8)-4-O-methyl-gallocatechin, Gallocatechin-3-O-galoyl-2-O-7,4(8)-4-O-methylgallocatechin, Myricetin-O-(O-galoyl)-hexoside, Myricetin-3-O-galactoside, Myricetin-galoyl-rhamnoside, Quercetin-3-O-(2-galoyl)-rhamnoside, Myricetin-3-O-acetyl-rhamnoside, Myricetin-3-O-rhamnose-3-O-rhamnoside, (Epi)gallocatechin-3-O-(3,5-O-dimethyl)-gallate, and 4-methyl-(epi)gallocatechin-3-O-)-gallate, none of these substances follow the Lipinski rules, they showed strong hydrophilicity, which may occur due to high degrees of acceptors and low degrees of hydrogen donors, all of which have a polar surface area greater than 140 A² and low logP, this is still correlated with low intestinal absorption and low permeability for Caco2 and MDCK cells, which corroborate their low oral bioavailability. The compounds showed greater toxicity in more complex organisms (Medaka and Minnow fish), but in simpler organisms they did not show toxicity (algae and Daphnia). All substances have strong antioxidant activity, are free radical scavengers, chemopreventive, anticarcinogenic and antineoplastic, this activity may be correlated with the reduction of reactive oxygen species, preventing them from causing DNA damage and, consequently, carcinogenesis. The substances seem to be promising for anticancer activity, and studies are needed to elucidate the mechanism of action of these substances.